Letter to the Editor concerning “Impact of preoperative mental health disorders on postoperative outcomes in patients with adolescent idiopathic scoliosis undergoing surgery” by Vallee EK, et al. (Spine Deformity [2026]: doi:10.1007/s43390-026–01288-z) - Kishankumar Mahida; Snehal Rajendra Jagtap (Spine Deformity, 2026)
Structural inequities and social determinants influence vaccination rates and related health outcomes. In 2025 in the USA, reduced federal funding for state and local vaccination programs and revised FDA COVID-19 vaccine policy have created new logistical and financial barriers to immunization, particularly for patients already facing limited access to care. This perspective highlights the role hospitals can play in reducing these barriers, through an example case study of a large academic medical center in Phoenix, AZ. Although this hospital routinely offers pneumococcal and annual influenza vaccines to inpatients, it has elected not to offer COVID-19 vaccines. To evaluate this potential missed opportunity, we conducted a retrospective review of more than 33,700 adult patients, analyzing COVID-19 vaccination rates and identifying independent risk factors for being unvaccinated, including measures of social determinants of health. We integrate findings from this retrospective analysis with global public health and medical literature to highlight the significant impact that health systems can have on improving vaccine access and uptake for patients experiencing health disparities.